Investigation of biogas generation potential during digestion of food waste - Matveev, Yu.; Kutsyi, D. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2016)
Approximately 4.2 mill tons of food waste generated annually in Ukraine. Most of the food waste is landfilled with a subsequent generation of landfill gas (LFG). Food waste is one of the main sources of LFG in Ukraine. The quantity of the generated LFG and methane can be evaluated based on the first order decay equation. For this purpose, the reliable data regarding methane generation potential and methane generation rate constant is needed. At this study, these parameters were evaluated based on the results of the anaerobic digestion of modeled mixture of food waste in laboratory reactor (lysimeter) at 35±2°C temperature. The component content of the modeled mixture was obtained from the available literature data. The average moisture content (MC) and volatile solids (VS) of the mixture were 78.9 and 17.3%, respectively. The obtained methane generation potential of the modeled mixture equals 64.4 nm3/t of food waste. The methane content in LFG was between 50% and 75% during all methane generation period. Obtained methane generation potential of the modeled mixture is lower by 7.7% than recommended values for the calculation of methane emissions in the National Inventory of green gas emission of Ukraine. It is obvious that a single experiment cannot be the basis for the revision of the calculations performed in the preparation of national inventories. It is necessary to extend the number of experimental data, including the application of the method described in this paper. As an object of research can be used food waste, taken from the general solid waste stream at the sorting lines, food waste separately collected in the locations of waste generation (cafeterias, supermarkets) as well as mixtures of various model mixtures. Methane generation rate constant was estimated to be 3,28 1/year. This figure represents laboratory condition only. The obtained experimental value of artificial conditions created in an experimental reactor and is not specific to conditions of real dumps and landfills. However, information about the rate of organic matter decomposition may be useful for drawing up the program of subsequent measurements. To determine the rate of methane production, typical conditions of landfills and dumps of solid waste, it is necessary to conduct additional studies in situ. The result of this study indicates that the obtained methane generation potential is lower than the data recommended by National Inventory Report of Ukraine. It could be used for the calculation of methane emission. However, the additional investigation should be recommended to conduct.